1983
DOI: 10.1002/1097-0142(19830101)51:1<97::aid-cncr2820510120>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Copper and copper-binding protein in fibrolamellar liver cell carcinoma

Abstract: Analysis of tissue from a recent case of fibrolamellar liver cell carcinoma by several staining and spectrophotometrc methods demonstrated elevated copper and copper‐binding protein (CBP) in malignant hepatocytes. Production of CBP has not previously been described for this or any other type of hepatocellular carcinoma. Identification of CBP in liver cell carcinoma adds further evidence that this protein is a normal synthetic product of liver cells which may reappear in chronic cholestasis or hepatic malignanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Satellite nodules may also be present. Abundance of fibrosis distributed in bands or laminae (hence fibrolamellar) is a hallmark of this neoplasm [68,69,70,71,72].…”
Section: Fibrolamellar Carcinomamentioning
confidence: 99%
“…Satellite nodules may also be present. Abundance of fibrosis distributed in bands or laminae (hence fibrolamellar) is a hallmark of this neoplasm [68,69,70,71,72].…”
Section: Fibrolamellar Carcinomamentioning
confidence: 99%
“…Cholestasis is often present in FLC [10], with canalicular bile plugging the most common cholestatic pattern. Because of the frequent cholestasis, FLC commonly has copper deposition [2, 10, 69, 73, 75, 76]. Of note, copper accumulation is also common in ordinary HCC that is cholestatic and is not a defining feature of FLC [77].…”
Section: Tumor Findingsmentioning
confidence: 99%
“…FLCs commonly involve regional lymph nodes [23, 45, 92], including the celiac nodes [45, 92], gastric nodes [65], and para-aortic nodes [45, 65]. Direct extension into the stomach [65], diaphragm [12], and pancreas [12, 76] have all been reported. Metastatic disease to intra-abdominal organs, as well as peritoneal spread, is common [12, 19, 36, 45, 66, 71, 96].…”
Section: Tumor Findingsmentioning
confidence: 99%
“…In the fibrolamellar type, using immunohistochemical techniques, only the production of AAT has been reported (Lack et al 1983, Lefkowitch et al 1983), but we have also detected the presence of AFP, and FER.…”
Section: Discussionmentioning
confidence: 93%
“…In one of these, copper and copper-binding protein were detected in neoplastic cells by staining and spectrophotometric methods and alpha,-antitrypsin by immunohistochemical study (Lack et af. 1983, Lefkowitch et al 1983; other markers sometimes present in liver neoplasms were not found. Five previous ultrastructural studies concerning this tumour have also been published (Craig et al 1980, Farhi et al 1982, 1983, An et al 1983, Guix-Pericas et af.…”
Section: Introductionmentioning
confidence: 99%